State of the art: understanding and integration of the social context in diabetes care. Issue 3 (24th January 2020) - de Wit, M.; Trief, P. M.; Huber, J. W.; Willaing, I.
Abstract: We review the past 25 years of research addressing challenges people living with diabetes experience in their daily lives related to social contexts, i.e. in their family, at work and in society at large, and identify research gaps. We found that young people with diabetes, as they develop through to adulthood, are exposed to considerable risks to their physical and mental health. Family‐system interventions have had mixed outcomes. Research in this area would benefit from attention to ethnic/cultural diversity, and involving fathers and other family members. In adults with diabetes, social support relates to better diabetes outcomes. While family member involvement in care is likely to affect health and psychosocial outcomes of the person with diabetes, key elements and mediators of effective family interventions need to be identified. The challenges of diabetes management at work are under‐researched; distress and intentional hyperglycaemia are common. When depression is comorbid with diabetes, there are increased work‐related risks, e.g. unemployment, sickness absence and reduced income. Research to support people with diabetes at work should involve colleagues and employers to raise awareness and create supportive environments. Stigma and discrimination have been found to be more common than previously acknowledged, affecting self‐care, well‐being and access to health services. Guidance on stigma‐reducing choice of language has been published recently. Resilience, defined as successful adaptation to adversity such as stigma and discrimination, requires studies relevant to the specific challenges of diabetes, whether at diagnosis or subsequently. The importance of the social context for living well with diabetes is now fully recognized, but understanding of many of the challenges, whether at home or work, is still limited, with much work needed to develop successful interventions. What's new?: The biopsychosocial model and social ecological theory posit that understanding of the 'interpersonal context of illness' will lead to interventions that will improve health outcomes. The last 25 years of psychosocial research have shown that the social context of people with diabetes is of great importance to clinical, behavioural and psychological outcomes. Social support and resilience are beneficial, whereas stigma and discrimination negatively impact self‐care, self‐esteem and emotional well‐being. Professionals should be mindful of the social context of diabetes throughout the lifespan. Development and implementation of research‐based interventions are needed to support people with diabetes at the interpersonal and societal/environmental levels. Workplaces and diabetes services and organizations need to develop a culture of support for people with diabetes and strive to minimize stigmatization and foster stigma resistance.